NILAI POSITIF TAYANGAN TELEVISI MENURUT KELUARGA BUDDHIS DI KABUPATEN KARANGANYAR - Situ Asih (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
This article aims to describe the television shows that are the favorite of Buddhist families in Karanganyar Regency, and the most frequently used broadcasting hours for watching and how Buddhist families view the positive value of television shows. The research method used in this research is a case study. The research was conducted in Karanganyar Regency. The research data were obtained from interviews, documentation studies, participatory observations and direct observations. The results showed that the most accessible communication media was television. The time most often used to access is at 17.00 WIB - 23.00 WIB. The programs that become the favorites of the father's group are sports and news shows, the programs that become the favorites of the mother's group are soap operas and news, while the programs that become the favorite shows of the younger generation are infotainment shows. The positive values ​​that can be taken from television shows that are consumed by the Buddhist community include being diligent and diligent in worshiping, Tepo Sliro and love of peace.